1997
DOI: 10.1002/(sici)1097-0142(19971201)80:11<2075::aid-cncr6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic radiosurgery for patients with nonsmall cell lung carcinoma metastatic to the brain

Abstract: Stereotactic radiosurgery for NSCLC brain metastases is effective and is associated with few complications. The early detection of brain metastases and treatment with radiosurgery combined with radiation therapy provide the opportunity for extended high quality survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(54 citation statements)
references
References 45 publications
3
47
2
1
Order By: Relevance
“…Kim et al (1997) reported on 77 patients with 115 metastases from non-small-cell lung cancer. Seventy-one patients also received whole brain radiation therapy (mean dose, 34 Gy; range, 15±56 Gy).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al (1997) reported on 77 patients with 115 metastases from non-small-cell lung cancer. Seventy-one patients also received whole brain radiation therapy (mean dose, 34 Gy; range, 15±56 Gy).…”
Section: Resultsmentioning
confidence: 99%
“…To do so, reports containing information on the in¯uence of``activity of extracranial disease'' on overall survival were identi®ed in the English language literature using computer and manual search. During the search, it was recognised that while the majority of reports use this particular term (Alexander et al 1995;Auchter et al 1996;Engenhart et al 1993;Joseph et al 1996;Kim et al 1997;Mori et al 1998;Shiau et al 1997), others use similar terms, such as``extracranial disease'' or``extracranial tumour'' (Breneman et al 1997;Kocher et al 1998, Pirzkall et al 1998Shu et al 1996;Cho et al 1998) which may imply the addition of the activity of uncontrolled primary tumour, too. Whatever is meant by the latter two terms, for the purpose of this review it is assumed that the substantial part of that in¯uence is coming from wide-spread distant metastases, which would be equal to the term``extracranial metastases''.…”
Section: Methodsmentioning
confidence: 99%
“…This median survival was less impressive than that achieved by the group who underwent SRS for BM from other primary cancers (lung, 10 months; renal cell, 11 months; breast, 13 months; melanoma, 7 months). [32][33][34][35] The local control rate was 84% and there were few side effects. However, the patients in that study who had active extracranial disease had a median survival of only 2 months after SRS.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is indisputable that accurate identifi cation of cerebral metastases is important for staging or restaging, predicting prognosis, and determining appropriate therapy [1][2][3].…”
mentioning
confidence: 94%